Implementasi Akuntansi Agrikultur Pada Badan Usaha Milik Desa (BUM Desa) Kencana Mandiri Desa Tanjung Belit - Neli Agustin; Fachroh Fiddin (Politeknik Negeri Bengkalis, 2020)
This research purpose to find out the recognition, measurement, and disclosure of biological assets and agricultural products in accordance with PSAK 69 at BUM Desa Kencana Mandiri. The types of data used in this study are quantitative and qualitative data. Data collection techniques are interviews and documentation. This type of research is qualitative research. As for the results of the research shows that BUM Desa Kencana Mandiri has not made recognition, measurement, and disclosure of biological assets or agricultural products in accordance with PSAK 69, this is seen from the absence of the presentation of biological asset accounts or agricultural products on the balance sheet that has been presented by the treasurer of BUM Desa Kencana Mandiri.